STUDI PEMANFAATAN LIMBAH TANDAN KOSONG KELAPA SAWIT OLEH MASYARAKAT DI JORONG KOTO SAWAH NAGARI UJUNG GADING KECAMATAN LEMBAH MELINTANG - Salmina, Salmina (Program Studi Pendidikan Geografi STKIP PGRI Sumatera Barat, 2016)
This study aims to know waste utilization of oil palm empty fruit bunches in Jorong Koto Sawah Nagari Ujunggading District Of Lembah Melintang West Pasaman. This type of research is descriptive. The population is head of the family in Jorong Koto Sawah Nagari Ujunggading District of Lembah Melintang totaled 1141 households. Samples were taken by purposive sampling region (designation) with 3 Jorong Koto Sawah 1) Dusun Banjar Kapar, 2) Dusun Muara Simpang, 3) Dusun Tanjung Harapan which has the highest number of people in Jorong Koto Sawah. The sample of respondents was taken with the proportion of 25% of the number of households, so that a population of 100 families. Data collection through questionnaires or instruments. Techniques of analysis using the analysis of the percentage formula. The research found that: (1) Awareness of the utilization of waste palm empty fruit bunches are in less good criteria, with a percentage of 56,8%, (2) Public Participation on the utilization of waste oil palm empty fruit bunches are in less good criteria, with a percentage of 56,9%, and (3) Motivation Communities to the utilization of waste oil palm empty fruit bunches are in the criteria is not good, with a percentage of 53.5%